The role of RNA adenosine demethylases in the control of gene expression - Rajecka, Veronika; Skalicky, Tomas; Vanacova, Stepanka (Biochimica et biophysica acta. Gene regulatory mechanisms, 2019)
RNA modifications are being recognized as an essential factor in gene expression regulation. They play essential roles in germ line development, differentiation and disease. In eukaryotic mRNAs, N6-adenosine methylation (m6A) is the most prevalent internal chemical modification identified to date. The m6A pathway involves factors called writers, readers and erasers. m6A thus offers an interesting concept of dynamic reversible modification with implications in fine-tuning the cellular metabolism. In mammals, FTO and ALKBH5 have been initially identified as m6A erasers. Recently, FTO m6A specificity has been debated as new reports identify FTO targeting N6,2'-O-dimethyladenosine (m6Am). The two adenosine demethylases have diverse roles in the metabolism of mRNAs and their activity is involved in key processes, such as embryogenesis, disease or infection. In this article, we review the current knowledge of their function and mechanisms and discuss the existing contradictions in the field. This article is part of a Special Issue entitled: mRNA modifications in gene expression control edited by Dr. Soller Matthias and Dr. Fray Rupert.
Keywords: RNA Processing, Post-Transcriptional; Humans; ALKBH5; RNA modification; m(6)A(m); RNA demethylase; m(6)A; zvířata; RNA; FTO; Adenine; Animals; AlkB Homolog 5, RNA Demethylase; alfa-ketoglutarát-dependentní dioxygenasa, AlkB homolog 5; adenin; lidé; posttranskripční úpravy RNA